Expectancy Theory Analysis to Conduct Research at Malaysian Research University - Bin Ramli, Mohammad Shakir; Jusoh, Ahmad Bin (International Journal of Economics and Financial Issues, 2015)
This paper presents a study for analyzing and improving research productivity of Malaysian Research University (RU). In literature there are various general models for research and development analysis. Although many prior researchers have studied factors that influence research productivity, only a few have examined it from the behavioral perspective. From the behavioral perspective, it becomes apparent that motivation theory is the predominant theory that researchers utilized when studying research productivity. Further scrutinized of the previous studies have identified that the expectancy theory analysis was used by most of them either solely or with other theories. It has been proven that the expectancy theory when properly employed will most likely bring success to organizational change. This paper addresses the development of the proposed model to be applied at Malaysian RU. Keywords: Expectancy Theory, Malaysian Research University, Research Productivity JEL Classifications: I2, O3